Composite Materials Engineering, Volume 1 Fundamentals of Composite Materials - Yi, Xiao-Su.; Du, Shanyi; Zhang, Litong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book is the first of two volumes providing comprehensive coverage of the fundamental knowledge and technology of composite materials. It covers a variety of design, fabrication and characterization methods as applied to composite materials, particularly focusing on the fiber-reinforcement mechanism and related examples. It is ideal for graduate students, researchers, and professionals in the fields of Materials Science and Engineering, and Mechanical Engineering.
An Introduction to Composite Materials -- Fiber Reinforcement -- Polymer Matrix Materials -- Composite Structure Design and Analysis -- Composite Property Testing, Characterization and Quality Control.
Keywords: Building materials; Polymers; Materials -- Analysis; Mechanics, Applied; Solids; Structural Materials; Polymers; Characterization and Analytical Technique; Solid Mechanics